Clinical diagnosis of partial or complete anterior cruciate ligament tears using patients' history elements and physical examination tests. - Simon Décary; Michel Fallaha; Sylvain Belzile; Johanne Martel-Pelletier; Jean-Pierre Pelletier; Debbie Feldman; Marie-Pierre Sylvestre; Pascal-André Vendittoli; François Desmeules (PLoS ONE)
Objective To assess the diagnostic validity of clusters combining history elements and physical examination tests to diagnose partial or complete anterior cruciate ligament (ACL) tears. Design Prospective diagnostic study. Settings Orthopaedic clinics (n = 2), family medicine clinics (n = 2) and community-dwelling. Participants Consecutive patients with a knee complaint (n = 279) and consulting one of the participating orthopaedic surgeons (n = 3) or sport medicine physicians (n = 2). Interventions Not applicable. Main outcome measures History elements and physical examination tests performed independently were compared to the reference standard: an expert physicians' composite diagnosis including history elements, physical tests and confirmatory magnetic resonance imaging. Penalized logistic regression (LASSO) was used to identify history elements and physical examination tests associated with the diagnosis of ACL tear and recursive partitioning was used to develop diagnostic clusters. Diagnostic accuracy measures including sensitivity (Se), specificity (Sp), predictive values and positive and negative likelihood ratios (LR+/-) with associated 95% confidence intervals (CI) were calculated. Results Forty-three individuals received a diagnosis of partial or complete ACL tear (15.4% of total cohort). The Lachman test alone was able to diagnose partial or complete ACL tears (LR+: 38.4; 95%CI: 16.0-92.5). Combining a history of trauma during a pivot with a "popping" sensation also reached a high diagnostic validity for partial or complete tears (LR+: 9.8; 95%CI: 5.6-17.3). Combining a history of trauma during a pivot, immediate effusion after trauma and a positive Lachman test was able to identify individuals with a complete ACL tear (LR+: 17.5; 95%CI: 9.8-31.5). Finally, combining a negative history of pivot or a negative popping sensation during trauma with a negative Lachman or pivot shift test was able to exclude both partial or complete ACL tears (LR-: 0.08; 95%CI: 0.03-0.24). Conclusion Diagnostic clusters combining history elements and physical examination tests can support the differential diagnosis of ACL tears compared to various knee disorders.